PRODUCTIVITY ANALYSIS OF GRANDPARENT STOCK IN 21 WEEK AGE GROWING PHASE - Sumiarti, Sumiarti; Darwati, Sri; Afnan, Rudi; Muladno, Muladno (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
This research aimed to compare the productivity of GPS strains, namely Ross, Cobb, Hubbard, and Indian River in hens and males at 21 weeks of age. The research data was obtained from the results of an audit of the breeding company by the Directorate General of Livestock and Animal Health, Ministry of Agriculture, from November 2022 to March 2023. The results showed that the comparison of hen productivity in the four strains, namely (1) the Indian River strain had a high body weight compared to other strains, (2) the Hubbard strain has a higher depletion rate than the other strains, but this depletion rate does not reflect bad or bad genetics, but it reflects a high degree of selection, and (3) the Indian River strain has a higher uniformity level than other strains. The productivity of roosters is (1) the Indian River strain has a high body weight compared to other strains, (2) the Indian River strain has a higher depletion rate than the other strains, however, this depletion rate does not reflect bad or bad genetics, but it reflects high selection rate, and (3) Indian River strain has a higher uniformity level than other strains.